Design of the System for Dry and Wet Sludge Coupling Combustion for the Coal-Fired Boiler - Zhaojun FANG; Bingquan FENG; Yi PANG; Bo HU; Wei ZHAO (Zhongguo dianli)
It is a more preferable choice to process the household garbage with high-efficiency pollutant treatment facilities of coal-fired power generating units. Regarding a coal-fired power generating unit capable of firing both wet and dry sewage sludge (with the water contents of about 80% and 20% respectively) in the transformation project, this paper conducts the study on the odor and the sewage generated during the sludge drying process from the coupling combustion in the coal-fired boiler. Also it proposes the optimization design for their treatment system. The odor produced in the stages of receiving, drying and transportation of sludge is collected by the overall micro-negative pressure control of the workshop and the local negative-pressure pumping of the drying device, then through the secondary air bellows system fed into the boiler, and eventually eliminated completely after high temperature combustion. The condensed sewage is mixed into the domestic sewage with low organic pollutant concentration, then treated in the subsequent biochemical treatment process and finally flows into the intermediate water pool for the existing industrial wastewater and hence recycled without any external discharge. With these improvements, the potential secondary pollution that may occur in the process of sludge coupling disposal has been avoided. The design can provide references for the transformation project of other similar coal-fired boilers coupling with sludge disposal.